RETRACTED: Fabrication of ZnFe2O4 modified TiO2 hybrid composites for photocatalytic reduction of CO2 into methanol. (1st February 2021) - Tahir, Muhammad Suleman; Manzoor, Numair; Sagir, Muhammad; Tahir, M.B.; Nawaz, Tasmia
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). The article plagiarized part of the PhD thesis of Farukh Iqbal, that part of the thesis was subsequently published here: J Chem Technol Biotechnol 2020; 95: 2208–2221 https://doi.org/10.1002/jctb.6408 One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.